Extracardiovascular injury complications in Kawasaki disease - Jie Liu; Yuqin Huang; Suyuan Qin; Danyan Su; Bingbing Ye; Yusheng Pang (Wiley, 2022)
ABSTRACT Importance Patients with Kawasaki disease (KD) experience various extracardiovascular injury complications, which may affect their outcomes. Objective To investigate the incidence and clinical characteristics of extracardiovascular complications in children with KD. Methods The clinical data of patients diagnosed with KD in the First Affiliated Hospital of Guangxi Medical University from January 2003 to January 2021 were reviewed. The clinical characteristics and extracardiovascular complications were compared among patients stratified by age, intravenous immunoglobulin (IVIG) therapy responsiveness, and coronary status. Results A total of 511 patients with KD were included, 357 (69.9%) were aged 1-5 years. Children aged <1 year (21.5%) and boys (70.8%) were more likely to have coronary artery lesions (CALs). The incidence of incomplete KD was lowest in 1-5‐year‐old patients (19.6%). Involvement of the hematological system gradually decreased with age (<1 year, 51.8%; 1-5 years, 36.7%; >5 years, 29.5%), whereas the involvement of the joints gradually increased with age (<1 year, 2.7%; 1-5 years, 6.2%; >5 years, 20.5%). Nervous system involvement was more common in IVIG non‐responders (15.7% [13/83] vs. 5.4% [23/428], P = 0.001). However, there were no significant differences in extracardiovascular injury complications between patients with or without CALs. Interpretation KD can involve multiple organ injuries as well as cardiovascular complications, and nervous systerm involvement may be more common in patients unresponsive to IVIG.